Geochemical and mineralogical record of MIS3-2 from Lake Petén Itzá (PI-02 Site) Guatemala - Rodrigo Martínez-Abarca; Michelle Abstein; Frederik Schenk; David A Hodell; Philipp Hoelzmann; Mark Brenner; Steffen Kutterolf; Sergio Cohuo; Laura Anahí Macario-González; Mona Stockhecke; Jason H Curtis; Flavio S Anselmetti; et al. (PANGAEA, 2023)
Inorganic geochemistry data (Ti, Al, Ca, Fe, and Mn) and mineralogy of sediments from Lake Petén Itzá are presented. Lake Petén Itzá was drilled in 2006 by the International Continental Discovery Program, obtaining seven lacustrine sedimentary records: PI-01, PI-02, PI-03, PI-04, PI-06, PI-7, and PI-9. Here, we present data from site PI-02 located north of the lake (16°59 extquotesingle58.04 extquotesingle extquotesingleN; 89°44 extquotesingle41.51 extquotesingle extquotesingleW) and measured between 67 and 19 m depth. Inorganic geochemistry data were obtained by X-ray fluorescence (XRF) using a Cox Analytical Itrax Core Scanner (Cr tube, 30 kV, 55 mA, 15 s exposure) with a resolution of 1 cm. XRF data is displayed in counts per second (cps). Subsequently, a transformation to centered log-ratio (CLR) was performed. The CLR data were obtained by dividing each value by the geometric mean of the elements measured at said depth, then the natural logarithm of said quotient was obtained. CLR results have no units. The mineralogy data were obtained every 1 m by ray diffraction (XRD) using a Rigaku MiniFlex 600 equipment (15 mA/40kV) in a rotation axis between 3 and 80°. The XRD values are in relative percentages obtained using the X-Pert High Score software (version 1.0b) and the diffraction potential files of the International Center for Diffraction Data, USA. Depth data corresponds with the master composite sequence presented by Mueller et al. (2010), while age data belongs to the age-depth model presented by Martínez-Abarca et al. 2023.